2021
DOI: 10.48162/rev.39.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Coffea canephora genotypes for leaf nutrient concentration

Abstract: This study analyzed the genetic diversity in Coffea canephora genotypes by univariate and multivariate statistical analysis, based on concentrations of macro- and micronutrients in coffee leaves in the stages of pre-flowering and grain filling. The experiment was arranged in randomized blocks with three replications, in a 42x2 factorial design, in which factor one represented the evaluated genotypes and factor two the periods of leaf sampling, i.e., pre-flowering and grain filling. The data of leaf nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…The S contents in the leaves are found to have higher concentrations for grain filling and seed filling periods, as in the studies by Oliosi et al [10] and Silva et al [25]. The concentration of this macronutrient showed variations due to the maturation of the genotypes.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The S contents in the leaves are found to have higher concentrations for grain filling and seed filling periods, as in the studies by Oliosi et al [10] and Silva et al [25]. The concentration of this macronutrient showed variations due to the maturation of the genotypes.…”
Section: Discussionsupporting
confidence: 52%
“…The formation of groups by the dendrogram indicates variability among the C. canephora genotypes for nutritional contents of leaves, flowers, grains, and straw. Silva et al [25], Gomes et al [8], and Martins et al [2] also observed divergence between the conilon coffee genotypes for nutrient concentration. These studies are essential for improvement programs, being used to select genotypes with superior characteristics.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Evaluation studies conducted by [ 4 , 8 , 13 , 15 ] with nutrient concentrations in different organs (leaf, flowers, grains, husk, fruits) of conilon coffee also reported values higher than 20% for some nutrients. Factors such as size of the experiment, maturation cycle and genotype response to biotic and abiotic factors may have contributed to the high indices [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 2019/2020 harvest, the country had an average productivity of 3.321 kg ha -1 , resulting from a production of 118.8 million tons of grain in 35,760.4 thousand hectares of land. During this harvest, the cultivated area increased by 1.7% relative to the past harvest (2,10), due to the expansion of the agricultural frontier with the exploration of the Brazilian semiarid region. Considering the need for irrigation, as well as the high temperatures that prevail in the semi-arid region, this expansion may constitute an opportunity for the diversification of crops in the region, particularly for seed production since irrigated crops require greater investment.…”
Section: Introductionmentioning
confidence: 99%